Interordinal gene capture, the phylogenetic position of Steller's sea cow based on molecular and morphological data, and the macroevolutionary history of Sirenia - Springer, Mark S.; Signore, Anthony V.; Paijmans, Johanna L. A. (Dr.); Velez-Juarbe, Jorge; Domning, Daryl P.; Bauer, Cameron E.; He, Kai; Crerar, Lorelei; Campos, Paula F.; Murphy, William J.; Meredith, Robert W.; Gatesy, John; et al. (Molecular Phylogenetics and Evolution, 2015)
The recently extinct (ca. 1768) Steller's sea cow (Hydrodamalis gigas) was a large, edentulous North Pacific sirenian. The phylogenetic affinities of this taxon to other members of this clade, living and extinct, are uncertain based on previous morphological and molecular studies. We employed hybridization capture methods and second generation sequencing technology to obtain >30 kb of exon sequences from 26 nuclear genes for both H. gigas and Dugong dugon. We also obtained complete coding sequences for the tooth-related enamelin (ENAM) gene. Hybridization probes designed using dugong and manatee sequences were both highly effective in retrieving sequences from H. gigas (mean = 98.8% coverage), as were more divergent probes for regions of ENAM (99.0% coverage) that were designed exclusively from a proboscidean (African elephant) and a hyracoid (Cape hyrax). New sequences were combined with available sequences for representatives of all other afrotherian orders. We also expanded a previously published morphological matrix for living and fossil Sirenia by adding both new taxa and nine new postcranial characters. Maximum likelihood and parsimony analyses of the molecular data provide robust support for an association of H. gigas and D. dugon to the exclusion of living trichechids (manatees). Parsimony analyses of the morphological data also support the inclusion of H. gigas in Dugongidae with D. dugon and fossil dugongids. Timetree analyses based on calibration density approaches with hard- and soft-bounded constraints suggest that H. gigas and D. dugon diverged in the Oligocene and that crown sirenians last shared a common ancestor in the Eocene. The coding sequence for the ENAM gene in H. gigas does not contain frameshift mutations or stop codons, but there is a transversion mutation (AG to CG) in the acceptor splice site of intron 2. This disruption in the edentulous Steller's sea cow is consistent with previous studies that have documented inactivating mutations in tooth-specific loci of a variety of ...